Fresno-Djambul Sister Cities' Reception at Fresno City Hall - Watkins, Howard::::::::: (1989)
Conference room gathering: Rolfe Gadebusch, Ruth Gadebusch, Djambul Mayor, Chris Petersen, Councilmember Chris Petersen, FUSD Board member Juan Arambula and Amy Arambula